Evolution of geochemical variations along the Central American volcanic front. (4th October 2013) - Saginor, Ian; Gazel, Esteban; Condie, Claire; Carr, Michael J.
<x xml:space="preserve">Abstract</x> [1] New geochemical analyses of volcanic rocks in El Salvador add to existing data from Nicaragua and Costa Rica to create a comprehensive set of geochemical data for Central American volcanics. These data coupled with previously published 40Ar/39Ar ages covering the past 30 Ma show that Costa Rica and Nicaragua had similar U/Th and Ba/La values until 10 Ma when the region developed the distinctive along arc variations that made this margin famous. U/Th values increased in Nicaragua since the Miocene, while remaining unchanged along the rest of the volcanic front. This coincides temporally with the Carbonate Crash, which caused a transition in Cocos plate sediments from low‐U carbonates to high‐U, organic rich hemipelagic muds. Increases in uranium are not observed in Costa Rica because its lower slab dip produces a more diffuse zone of partial melting and because of the contribution from Galapagos‐derived tracks dilutes this signal. Ba/La has been used as a geochemical proxy for contributions from the subducting slab; however, our analyses indicate that the Ba concentrations do not vary significantly along strike either in the subducting sediment or the volcanic front. Along‐arc variation is controlled by changes in La, an indicator of the degree of partial melting or source enrichment. Trace element models of five segments of the volcanic front suggest that a subducting sediment component is more important to magmas produced in El Salvador and Nicaragua than in Costa Rica, where the geochemistry is controlled by recent (<10 Ma) recycling of Galapagos tracks.